2020
DOI: 10.5483/bmbrep.2020.53.8.031
|View full text |Cite
|
Sign up to set email alerts
|

Bee venom inhibits the proliferation and migration of cervical-cancer cells in an HPV E6/E7-dependent manner

Abstract: Bee venom (BV), secreted from the venom gland of the honey bee, contains several biological active compounds. BV has been widely used as a traditional medicine for treating human disease, including cancer. In this study, we have shown the molecular mechanism underlying the therapeutic effect of BV on cancer. Treatment with BV reduced the proliferation of cervical-cancer cells in a dose-and time-dependent manner. Interestingly, the killing effect of BV was specific to HPVpositive cervical-cancer cell lines, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…3T3-L1 cells were transfected with mouse galectin-1 siRNA (50 nM) using Lipofectamine RNAiMAX (Invitrogen, Carlsbad, CA, USA), according to the manufacturer's protocol. After 24 h, the medium was replaced with maintenance medium supplemented with 10% calf serum 38,39 .…”
Section: Sirna Transfectionmentioning
confidence: 99%
“…3T3-L1 cells were transfected with mouse galectin-1 siRNA (50 nM) using Lipofectamine RNAiMAX (Invitrogen, Carlsbad, CA, USA), according to the manufacturer's protocol. After 24 h, the medium was replaced with maintenance medium supplemented with 10% calf serum 38,39 .…”
Section: Sirna Transfectionmentioning
confidence: 99%
“…BV demonstrated the ability to inhibit the growth and migration of HPV-positive cervical cancer Caski and HeLa cells, and cell cycle protein Cyclin A and Cyclin B, Akt, JNK and p38/44/42 and their phosphorylated proteins associated with mitogenic signaling pathways were inhibited, and pro-Caspase-3, pro-Caspase-9, cleaved polyadenosine-diphosphate-ribose polymerase (PARP), Bcl-2 and Bcl-xL expression was reduced. On the contrary, proteins such as p53, p21, and retinoblastoma (Rb) were upregulated in expression with the utility of BV, and the number of dead and apoptotic cells was significantly promoted ( Kim D. H. et al, 2020 ). It is worth noting that the main mode of death of HeLa cells after BV treatment is apoptosis, which causes severe cell membrane damage and cell shrinkage ( Borojeni et al, 2020 ), while MEL can show the effect of inhibiting HeLa cell proliferation and inducing apoptosis such as cell shrinkage and structural disorganization ( Zarrinnahad et al, 2018 ).…”
Section: Anticancer Effectsmentioning
confidence: 99%
“…Notably, melittin and its extract hybrid peptides have demonstrated anti-tumor effects in tumorderived cell lines (23)(24)(25)(26). It has been reported that crude bee venom and melittin exhibited the inhibition capability in several cancer cell lines such as melanoma, colon, breast, and cervical cancer cells (27)(28)(29)(30). Due to the wide range of biological properties, bee venom attracts more and more attention.…”
Section: Original Articlementioning
confidence: 99%